Sewage pollution: genotoxicity assessment and phytoremediation of nutrients excess with Hydrocotyle ranunculoides - Basílico, Gabriel; Magdaleno, Anahí; Paz, Marta; Moretton, Juan; Faggi, Ana; de Cabo, Laura (Environmental monitoring and assessment, 2017)
The discharge of sewage effluents into low-order streams has negative effects on water quality. Macrophytes can be efficient in the treatment of this wastewater due to the removal of the main pollutants. The genotoxicity of sewage-polluted water discharging into La Choza stream was evaluated by testing with Allium cepa . Also, a phytoremediation assay with continuous recirculation of the residual water was conducted for 12 days. Three treatments were carried out. One treatment (Hr) was performed with a macrophyte ( Hydrocotyle ranunculoides ), and two treatments were conducted without macrophytes: with lighting (Ai) and without lighting (Ao). The wastewater was toxic according to all the evaluated indexes (mitotic index, frequency of chromosomal aberrations and micronucleus). High concentrations of ammonium, dissolved inorganic nitrogen (DIN), total (TP) and soluble reactive phosphorous (SRP) and indicators of faecal contamination were determined in the wastewater. The ammonium, DIN, SRP and TP loads at the end of the assay were significantly lower in the treatments with light (Hr and Ai). So, the nutrient removal was due to their absorption and adsorption by the periphyton and H. ranunculoides . Our results lead us to recommend the maintenance and planting of macrophytes in lowland streams subject to sewage pollution.